Associations of self-reported residential noise exposure with obesity and hypertension in children and adolescents - Liang, Xiaohua; Tang, Xian; Liu, Mingliang; Liang, Xiaoyue; Chen, Li; Chen, Xia; Zuo, Lei; Ren, Yanling; Hao, Guang (Frontiers in Pediatrics, 2022)
Background Epidemiologic evidence linking environmental noise to obesity and hypertension remains scarce, especially in children, and the results remain inconclusive. This study aims to examine the cross-sectional associations of self-reported residential noise exposure with obesity and hypertension in children and adolescents. Methods As an ongoing study, a representative sample of the children aged 6–9 years in Chongqing were selected in 2014. In 2019, self-reported residential noise (answer categories: “very quiet,” “moderately quiet,” “slightly quiet,” and “not at all quiet”) data were collected, and 3,412 participants with completed data were included in the analyses. Results Participants living in a quieter area had a significantly lower risk of obesity than those living in a noisy area (very quiet: OR = 0.50, 95%CI: 0.29–0.88, P = 0.015; moderately quiet: OR = 0.61, 95%CI: 0.36–1.02, P = 0.059). Similar associations were observed for abdominal obesity, although did not reach statistical significance. Consistently, residential noise exposure was significantly associated with body mass index (BMI) and waist-to-height ratio. Self-reported residential noise exposure was positively associated with systolic blood pressure (β = −1.808; 95%CI = −3.495, −0.110; P = 0.037). When sleep quality, study stress, BMI, and vegetable/fruits consumption were further adjusted, all effect estimates decreased, and no statistical association was observed between noise exposure and blood pressure. Furthermore, we found that the mediating effects of obesity on the associations of self-reported residential noise exposure with hypertension were 6.8% (% of total effect mediated = 0.068, 95%CI: −2.58, 3.99), although did not reach statistical significance. Conclusions Self-reported residential noise exposure was associated with a higher risk of obesity or abdominal obesity. Also, self-reported residential noise exposure was positively associated with hypertension, and obesity may partially mediate this association, but did not reach statistical significance.